Model perhitungan kompleksitas proses sangrai kopi menggunakan biji kopi tradisional Indonesia - Budiono, Hendri Dwi Saptioratri; Zuhuda, Rahman Muhamad; Fausta , Mohammad Anindya; Suputra , Oka Widiantara; Aditya , Trimitra Mahesa (BKS-TM Indonesia, 2023)
The manufacturing process involves converting raw materials into usable products, also applicable in other sectors like coffee roasting. Coffee roasting can be considered a manufacturing process as it involves transforming green coffee beans into roasted coffee beans. Coffee roasting defines 20% - 25% of coffee quality, making a variation in process is impactful. Due to various influential parameters, achieving specific bean specifications adds complexity to the process. Indonesia, a major coffee producer, emphasizes research for enhancing coffee quality, specifically for varieties like Arabica Gayo, Arabica Solok Radjo, Robusta Bengkulu, and Robusta Temanggung. Another underlying factor for this research is the lack of studies related to the complex process of coffee roasting. This research uses the model to calculate the complexity of the manufacturing system in the coffee roasting process. This model is used as a tool to assess the existing process. Furthermore, this model simplifies the calculation of the process complexity, and the resulting index can be used to estimate initial costs during the design phase for the roasting process. This research adopts the method by W.H. El Maraghy regarding complexity modeling and applies it to the scope of coffee roasting. Based on the conducted research, the most important aspects that influence the complexity of roasting coffee beans based on the roast level are roast color, mass, and dimensions resulting from the roast profile of coffee beans. Temanggung Robusta coffee beans were found to have the highest complexity index, with an RPM of 90 and a dark roast level of 9.21.